EFFECT OF VEGETARIAN DIET ON NUTRITIONAL STATUS IN SCHOOL-AGE CHILDREN - Ramadhitya, Amelia Sekar; Nopian, Dinda Putri; Laili, Farah; Azzahra, Aulia Ifitihtani; Nabila, Oktavia; Nikma, Fatikha Valent; Wahyurin, Izka Sofiyya (Universitas Airlangga, 2025)
A vegetarian diet is a pattern of food consumption that comes from plants in the form of vegetables, nuts, seeds, fruits, and does not or still consume dairy products and eggs. The implementation of a vegetarian diet in school-age children can have a positive impact on reducing the risk of certain diseases. In addition, the restriction of animal food sources causes vegetarians to be at risk of having a lower nutritional status. This literature review aims to analyze the effect of a vegetarian diet on the nutritional status of school-age children. The Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) approach was used in this literature review study. The steps taken consisted of identification, analysis, evaluation, classification and categorization of previously produced articles. Data and information sources were obtained through electronic databases published on Google Scholar, ProQuest, and Scopus. The selection category is articles that have been published in the last 10 years (2014-2024) and 251 journals were obtained. After several elimination processes, a total of 6 articles met the criteria to be selected. It was found that there was a significant difference based on BMI (p value<0.001), weight for height z-score (p=0.006 and p=0.103), BMI for age (p<0.001), and BMI (p = 0.004 and p = 0.001) in the effect of a vegetarian diet on the nutritional status of school-age children.